Improving Carton Packaging Yield in the Beverage Industry Using PDCA and Integrated Quality Tools - Sari, Ratna Wulan; Slamet, Alim Setiawan; Anggareni, Elisa (Jurnal Locus Penelitian dan Pengabdian, 2025)
In operations and production management, material yield is one of the key indicators of process efficiency and cost effectiveness. This study aims to identify the root causes of low carton packaging yield, formulate improvement strategies based on the PDCA (Plan–Do–Check–Act) cycle integrated with 16 structured quality management tools, and evaluate the effectiveness of this approach in addressing inefficiencies in carton packaging. To achieve this, root causes were identified using a Fishbone Diagram (4M1E), further analyzed with the 5 Whys method, and validated through the 3G approach (Genba, Genbutsu, Genjitsu). Key issues were prioritized using Failure Mode and Effects Analysis (FMEA). Improvement ideas were then generated using the SCAMPER technique and selected using a PICK Chart. The selected solutions were implemented using the 5W2H framework and scheduled with a Gantt Chart. To ensure sustainability, poka-yoke mechanisms and process standardization were applied. The implementation of targeted improvement strategies at one of Indonesia’s leading beverage companies led to a notable increase in carton packaging yield—from 99.44% to 99.75%—effectively closing the performance gap. This improvement was accompanied by a reduction of over 50% in measurable negative impacts across all PQCDSME dimensions (Productivity, Quality, Cost, Delivery, Safety, Morale, and Environment), reflecting enhanced process stability, operational efficiency, and cross-functional performance. This study demonstrates that integrating structured, data-driven problem-solving tools with the PDCA (Plan–Do–Check–Act) cycle can significantly improve manufacturing performance. The approach proved effective in reducing waste, increasing yield, and supporting continuous improvement within a production environment.